Karya Tulis Ilmiah Wajib UJI ORGANOLEPTIK PERMEN KARPEL INN (KARMIN + Piper betle Linn) SEBAGAI CEMILAN SEHAT - Muhammad Fathurrahman; M. Zainuddin; Septi Irianti (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2024)
This study aims to find solutions to the problem of the increasing spread of unhealthysnacks that contain ingredients that are not needed by the body. This study uses naturalfood coloring that is often found but rarely known, namely coloring derived fromcoechineal insects, namely carmine, and uses extracts from betel (Piper betle Linn) as aningredient that contains antibacterial and antioxidant properties that are good for the bodybut have a smell and taste that is less liked by the current generation. Therefore, betel leafextract which has a pungent aroma is turned into candy which is a snack that is liked by allcircles. In this study, an organoleptic test was carried out on the sample to determine thelevel of preference of the samples for candy with 4 different compositions.Keywords: Carmine, Betel leaf extract, Candy, Organoleptic test.